Pyrolysis and thermogravimetric study to elucidate the bioenergy potential of novel feedstock produced on poor soils while keeping the environmental sustainability intact - Ahmad, Muhammad Sajjad; Mehmood, Muhammad Aamer; Luo, Huibo; Shen, Boxiong; Latif, Muhammad; Wan Ab. Karim Ghani, Wan Azlina; Alkhattabi, Nuha Abdulhamid; Aloqbi, Akram Ahmed; Jambi, Ebtihaj Jamaluddin; Gull, Munazza; Rashid, Umer (MDPI, 2019)
This work focused on exploring the bioenergy potential of biomass produced on salt-affected soils by growing two types of grasses, namely Parthenium hysterophorus (carrot grass) and Pennesetum benthiumo (mott grass), without using fertilizers or pesticides. The whole plant biomass of both grasses was pyrolyzed at three heating rates (10, 30, and 50 °C min−1) in a joined Thermogravimetry–Differential Scanning Calorimetry (TGA–DSC) analyzer under an inert (nitrogen) environment. The pyrolysis of both grasses was shown to occur in a three-stage process, while most of the thermal transformation occurred at the temperature range of 240–400 °C. The pyrolytic behavior was assessed by estimating the kinetic parameters, using the isoconversional models of Kissenger–Akahira–Sunose and Ozawa–Flynn–Wall. The average values of the activation energy of carrot and mott grasses were shown to be 267 kJ mol−1 (R2 ≥ 0.98) and 188 kJ mol−1 (R2 ≥ 0.98), indicating the suitability of both grasses for co-pyrolysis. Whereas, the difference in the values of enthalpy change and the activation energy was shown to be <~5 kJ mol−1 at each fractional point, which indicated that the product formation was being favored. Moreover, the high heating values of carrot grass (18.25 MJ kg−1) and mott grass (18.63 MJ kg−1) have shown a remarkable bioenergy potential and suitability of co-pyrolysis for both grasses. This study will lead to establishing an energy-efficient and cost-effective process for the thermal transformation of biomass to bioenergy.